Mechanistic Insights Into the Cross-Feeding of Ruminococcus gnavus and Ruminococcus bromii on Host and Dietary Carbohydrates - Crost, Emmanuelle H.; Le Gall, Gwenaelle; Laverde-Gomez, Jenny A.; Mukhopadhya, Indrani; Flint, Harry J.; Juge, Nathalie (Frontiers in Microbiology, 2018)
Dietary and host glycans shape the composition of the human gut microbiota with keystone carbohydrate-degrading species playing a critical role in maintaining the structure and function of gut microbial communities. Here we focused on two major human gut symbionts, the mucin-degrader Ruminococcus gnavus ATCC 29149, and Ruminococcus bromii L2-63, a keystone species for the degradation of resistant starch in human colon. Using anaerobic individual and co-cultures of R. bromii and R. gnavus grown on mucin or starch as sole carbon source, we showed that starch degradation by R. bromii supported the growth of R. gnavus whereas R. bromii did not benefit from mucin degradation by R. gnavus. Further we analyzed the growth (quantitative PCR), metabolite production (1H-NMR analysis), and bacterial transcriptional response (RNA-seq) of R. bromii cultured with resistant starch (RS) or soluble starch (SS) in the presence or absence of R. gnavus. In co-culture fermentations on starch, 1H-NMR analysis showed that R. gnavus benefits from transient glucose and malto-oligosaccharides released by R. bromii upon starch degradation, producing acetate, formate, and lactate as main fermentation end-products. Differential expression analysis (DESeq 2) on starch (SS and RS) showed that the presence of R. bromii induced changes in R. gnavus transcriptional response of genes encoding several maltose transporters and enzymes involved in its metabolism such as maltose phosphorylase, in line with the ability of R. gnavus to utilize R. bromii starch degradation products. In the RS co-culture. R. bromii showed a significant increase in the induction of tryptophan biosynthesis genes and a decrease of VitB12-dependant methionine biosynthesis as compared to the mono-culture, suggesting that Trp and VitB12 availability become limited in the presence of R. gnavus. Together this study showed a direct competition between R. bromii and R. gnavus on RS, suggesting that in vivo, the R. gnavus population inhabiting the mucus niche may be modulated by the supply of non-digestible carbohydrates reaching the colon such as RS.